Back analysis of previously stooped Panels to improve the safety and productivity of future stooping operations at new Denmark colliery - Gonsalves, Ricardo (University of the Witwatersrand, Johannesburg, 2024)
New Denmark Colliery (NDC) is a Seriti-owned underground coal mine in the Mpumalanga Province. It started stooping operations towards the end of 2018 and has since stooped 50 panels safely across all three of its shafts. NDC selected the NEVID method, which is known for its safety and success in neighbouring mines. Initially stooping panels in the 1100 block, NDC encountered challenges due to narrow panel spans, leading to limited goafing and heightened abutment stresses on surrounding pillars and infrastructure. This necessitated additional support for strategic pillars to ensure long-term stability. To address these challenges, comprehensive research was conducted, which included back-analysis of stooped panels and numerical modelling. Findings revealed that goafing was influenced more by horizontal stress concentrators, such as geological structures than panel spans. Goafing at NDC has primarily been defined by low-angle shear failures, which only extend a couple of metres into the immediate sandstone roof. This is known as partial goafing, which typically results in high abutment stresses. Since complete goafing is unlikely due to the depth below surface and the competent roof material, the high abutment stresses needed to be managed by increasing the width of the barrier pillars between panels and leaving a sufficient number of stopper pillars at the end of a stooped panel. Numerical modelling was used to validate NDC's current design strategy of stooping panels and to determine the width of new barrier pillars. The derived strategy includes an increase in barrier pillar width and stand-off distances, to ensure the long-term stability of main developments. iv The current stooping strategy which was informed by comprehensive research and modelling, has proven effective in both safety and stability.
A research report submitted in fulfillment of the requirements for the Master of Science, In the Faculty of Engineering and the Built Environment , School of Mining Engineering, Industrial and Aeronautical Engineering, University of the Witwatersrand, Johannesburg, 2024
Keywords: UCTD; SDG-17: Partnerships for the goals